Factors Affecting Business Income of Empal Gentong in Cirebon City - Lathifa Dinar; Neni Widayaningsih; Diah Setyorini Gunawan; Joseph Yakatambu Yaramai (EKO-REGIONAL, 2021)
The goal of this research is to analyze the effect of capital, labor, length of business, education, and working hours on the empal gentong business income in Cirebon and to analyze which variable has the most effect on that income. We surveyed 30 business owners of empal gentong in Cirebon. The method using in this research is multiple linear regression. This result concludes capital, labor, length of business, education, and working hours have a positive and significant effect jointly on empal gentong business income. The analysis result in partially is capital and length of business have significant effect. Meanwhile, variables of labor, education and working hours have no significant effect on empal gentong business income. From these five variables, the most influential variable on empal gentong business income is the capital variable.Keywords: Income, Capital, Labor, Length of Business, Education, Working Hours